Hadith #2688 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Jubayr bin Mut'im; Ma'mar bin Rashid معمر بن راشد; Muhammad bin Jubayr bin Mut'im محمد بن جبير بن مطعم بن عدي; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان (Sunan Abi Dawud)
Anas said “Eighty Meccans came down from the mountain of Al Tan’im against the Prophet(ﷺ) and his Companions at the (time of the) dawn prayer to kill them. The Apostle of Allaah(ﷺ) took them captive without fighting and the Apostle of Allaah(ﷺ) set them free. Thereupon Allaah Most High sent down “He it is Who averted their hands from you and your hands from them in the valley of Makkah,” till the end of the verse.
Grade: Sahih